2005
DOI: 10.2223/jped.1368
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and intestinal iron absorption in children with chronic hepatic disease with and without cholestasis

Abstract: The cholestatic group showed more severe nutritional deficits. Despite the evidence of lower iron intestinal absorption, cholestatic patients responded to oral iron therapy, probably, due to the coexistence of iron deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
2
7
1
Order By: Relevance
“…Anemia of diverse etiology is a common manifestation associated with CLD [36]. We found a strong positive correlation between hemoglobin levels and most anthropometric parameters.…”
Section: Discussionsupporting
confidence: 51%
“…Anemia of diverse etiology is a common manifestation associated with CLD [36]. We found a strong positive correlation between hemoglobin levels and most anthropometric parameters.…”
Section: Discussionsupporting
confidence: 51%
“…The estimate of fat deposits through TST and of protein content by AMC and AC are complementary data that allow for an accurate nutritional evaluation of these patients. 3,21,22 In the present study, one-third of patients showed W/A and H/A indices under −2 Z-scores. Considering the W/H index, only 12.1% of patients had Z-score lower than −2; in relation to the BMI, the percentage was 16.5%.…”
Section: Discussionsupporting
confidence: 53%
“…Reduced skinfold thickness and arm circumference prior to reduction in weight and height have been shown in pediatric patients with malnutrition. This reduction occurs because the muscle provides the amino acids for gluconeogenesis and protein synthesis [10,11]. In chronic liver disease, the lower extremities and abdominal region are more prone to fluid accumulation than the upper extremities; therefore, SuST and other anthropometric measurements of the lower limbs are useless for the assessment of malnutrition, as shown in our study [2].…”
Section: Discussionmentioning
confidence: 84%
“…Sokol et al [10] found that most of the children with chronic liver disease were underweight and had stunted height, and approximately 60% of the children had depleted fat stores. Moreover, Mattar et al [11] divided the infants into two groups according to the presence of cholestasis and found that cholestatic infants exhibited more severe nutritional deficiency than the non-cholestatic infants. They found that 64.3% of the children with cholestatic liver disease had stunted height.…”
Section: Discussionmentioning
confidence: 99%